Induce estrus with ultrasonography examination and progesterone hormone assay for pregnancy diagnosis in Iraqi goats: A. KH. Taklan1, A. F. Alwan2 and S. M. Nada3 - Alwan, A. F. (The Iraqi Journal of Veterinary Medicine, 2017)
The aim of present work is to induce ovulation in 40 female goats in non-breeding seasons and pregnancy diagnosis using RIA of progesterone serum level and trans abdominal ultrasonography with 3.5 MHz prop. The 40 Iraqi goats were naturally inseminated during estrous phase, using fertile backs, after withdrawal of intravaginal impregnated sponges with 20 mg of cronolone (Fluorogestone Acetate progestagen) kept for eleven days and 400 IU of equine chorionic gonadotrophin inject I/M 24hrs. before sponge withdraw. The results indicated that all does were showed (100%) estrous sign, the estrous time was 24-66 hrs. after sponge withdrawal and the pregnancy rate 67.5%. Blood samples were collected from the jugular vein before progesterone treatment, at the time of insemination and after 21 day of insemination. Early pregnancy diagnosis by RIA of progesterone concentration was performed and showed progesterone hormone value as were increasing significantly (P<0.01) from 0.26±0.12 ng/ml before insemination to 3.29±1.10 ng/ml in 21 days after insemination. Pregnant animal was examined using transabdominal ultrasonography during 45, 60 and 90 days after insemination. In conclusion, estrus could be efficiently induced in female goats during non-breeding season using 20 mg cronolone impregnated sponge and 400 IU equine chorionic gonadotrophin I/M at 24 hrs. before spongy withdrawal. The effective of early detection of pregnancy by progesterone assay in 21 days after insemination and ultrasonography by abdominal 3.5 MHz transducer after 45 days of pregnancy.